Thermal Stresses -- Advanced Theory and Applications - Hetnarski, Richard B.; Eslami, M. Reza (Solid Mechanics and Its Applications,, 2009)
This book is intended as an advanced modern textbook and reference handbook on the topic of thermal stresses. It should serve a wide range of readers, in particular, graduate and postgraduate students, scientists, researchers in various industrial and government institutes, and engineers working in mechanical, civil, and aerospace engineering. This volume covers diverse areas of applied mathematics, continuum mechanics, stress analysis, and mechanical design. This work treats a number of topics not presented in other books on thermal stresses, for example: theory of coupled and generalized thermoelasticity, finite and boundary element method in generalized thermoelasticity, thermal stresses in functionally graded structures, and thermal expansions of piping systems. As the field of thermal stresses lies at the crossroads of stress analysis, theory of elasticity, heat conduction, and advanced methods of applied mathematics, all these subjects are dealt with in the book to the extent they are necessary. Thus, the book is self-contained, so that the reader should not need to consult other sources while studying the topic. The book starts from basic concepts and principles, and these are developed to more advanced levels as the text progresses. Nevertheless, some basic knowledge on the part of the reader is expected in classical mechanics, stress analysis, and mathematics, including vector and cartesian tensor analysis. .